2020
DOI: 10.3389/fninf.2020.00039
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Rich Club Organization of Hemispheric White Matter Networks in Bipolar Disorder

Abstract: Neuroimaging studies suggest disrupted connections of the brain white matter (WM) network in bipolar disorder (BD). A group of highly interconnected high-density structures, termed the 'rich club,' represents an important network for brain functioning. Recent works have revealed abnormal rich club organization in brain networks in BD. However, little is known regarding changes in the rich club organization of the hemispheric WM network in BD. Forty-nine BD patients and fifty-five age-and sex-matched normal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 80 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…Correspondingly, siblings of individuals with schizophrenia exhibit RC disruptions ( 33 ). Again, in individuals with bipolar disorder, findings have been more varied, with studies reporting unaltered ( 17 , 18 , 19 ), decreased ( 20 ), or increased ( 21 , 22 , 23 ) RC connectivity, and previous studies in BDo also presented no significant differences in RC connectivity ( 15 , 34 , 35 ) compared with Co. Our cross-sectional findings at time point 1 in child and adolescent offspring are consistent with these patterns, demonstrating suggestive evidence for lower RC connectivity only in SZo ( 34 ). Our analyses revealed a nonsignificant effect of familial risk of schizophrenia on the age trajectory of RC connectivity but in the same direction as cross-sectional findings and previous literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, siblings of individuals with schizophrenia exhibit RC disruptions ( 33 ). Again, in individuals with bipolar disorder, findings have been more varied, with studies reporting unaltered ( 17 , 18 , 19 ), decreased ( 20 ), or increased ( 21 , 22 , 23 ) RC connectivity, and previous studies in BDo also presented no significant differences in RC connectivity ( 15 , 34 , 35 ) compared with Co. Our cross-sectional findings at time point 1 in child and adolescent offspring are consistent with these patterns, demonstrating suggestive evidence for lower RC connectivity only in SZo ( 34 ). Our analyses revealed a nonsignificant effect of familial risk of schizophrenia on the age trajectory of RC connectivity but in the same direction as cross-sectional findings and previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature has demonstrated disruptions of the connectome—the comprehensive network of the brain’s structural connections—in individuals with bipolar disorder ( 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ) and schizophrenia ( 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ), as well as their siblings ( 33 ) and offspring ( 15 , 34 , 35 , 36 ). A recurrent finding in both patient groups ( 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 30 ) and their relatives ( 33 , 34 ) has been the aberrant connectivity of the brain network’s “rich club” (RC), a coherent constellation of highly interconnected hubs reputed to act as the backbone for global brain integration ( 37 , 38 , 39 ).…”
mentioning
confidence: 99%
“…Rich-club organization is a key characteristic of brain networks, and its existence has not only been found during human brain development (Sa de Almeida et al, 2021; van den Heuvel & Sporns, 2011), but also in numerous neurological diseases (Cao et al, 2014; Collin, Kahn, et al, 2014; Cui et al, 2022; D. Li et al, 2020; Liu et al, 2021; Peng et al, 2021; Ray et al, 2014; Van Den Heuvel et al, 2013). In our study, the rich-club network of densely interconnected hubs was observed for both APD and HC groups in the left fusiform gyrus, left precuneus, bilateral parietooccipital sulcus, bilateral hippocampus, bilateral basal ganglia (i.e., caudate, globus pallidus, putamen, nucleolus accumbens), and bilateral thalamus.…”
Section: Discussionmentioning
confidence: 99%
“…Rich-club organization is a key characteristic of brain networks, and its existence has not only been found during human brain development (Sa de Almeida et al, 2021;van den Heuvel & Sporns, 2011), but also in numerous neurological diseases (Cao et al, 2014;Collin, Kahn, et al, 2014;Cui et al, 2022;D. Li et al, 2020;Liu et al, 2021;Peng et al, 2021;Ray et al, 2014;.…”
Section: Rich-club Organization Is Intact In Apdmentioning
confidence: 99%